2020 Forum for Specification and Design Languages (FDL) 2020
DOI: 10.1109/fdl50818.2020.9232936
|View full text |Cite
|
Sign up to set email alerts
|

QRML: A Component Language and Toolset for Quality and Resource Management

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This work presents the development of an application for space exploration using a methodology [3] that allows the dynamic reconfiguration of the system. The purpose of the application is the identification of decommissioned satellite models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work presents the development of an application for space exploration using a methodology [3] that allows the dynamic reconfiguration of the system. The purpose of the application is the identification of decommissioned satellite models.…”
Section: Discussionmentioning
confidence: 99%
“…The system presented in this work is made up of various software components with functionalities including video processing, image coding, recognition and positioning of objects, among others. To implement and connect the components, a component implementation methodology [3] has been used that allows the system to reconfigure itself at runtime with different configurations (set points) that allow different performances and energy consumption strategies to adapt to the environmental conditions that might be encountered during a space mission.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…To design the new architecture and components we use Quality and Resource Management domain-specific Language (QRML) van den Berg et al [9] that defines domain specific language for QRM, and also provides an accompanying toolset. This toolset allows us to specify a QRML model, model visualization and generate C++ code templates for system and application monitoring.…”
Section: Architecture and Components Definitionsmentioning
confidence: 99%
“…The experiments and results presented in this work use a 3D acquisition system from Perez-Cortes et al [6] using a ZeroGravity 3D (ZG3D) device [8] as the one shown in Fig. 1 in combination with concepts introduced in the FitOptiVis project [7] to assist in the design of the new components and architecture using a component language and toolset for quality and resource management (QRML) Berg et al [9]. QRML enables specifying heterogeneous hardware/software systems and their composition and configurations conveniently.…”
Section: Introductionmentioning
confidence: 99%